Kant’s Prudential Theory of Religion: The Necessity of Historical Faith for Moral Empowerment - R. Palmquist, Stephen (Con-Textos Kantianos. International Journal of Philosophy, 2015)
Given his emphasis on deontological ethics, Kant is rarely regarded as a friend of prudence. For example, he is often interpreted as an opponent of so-called “historical faiths” (i.e., empirical religious traditions). What typically goes unnoticed is that in explaining the legitimate (indeed, indispensable) role of historical faiths in the moral development of the human race, Kant appeals explicitly to their prudential status. A careful examination of Kant’s main references to prudence demonstrates that the prudential status of historical faith is the key to understanding both its limitations (as merely the vehicle of true religion, not its essential core) and its real value (as a necessary means of moral empowerment). The wise person adopts some form of historical faith, because to abandon any and all prudential appeals to a faith-based vehicle for morality would render the goal of living a good life virtually impossible for embodied beings to achieve.